Urgensi Teknologi Pendidikan Islam Bagi Pesantren Dalam Menghadapi Perkembangan Zaman - Silviana Putri Kusumawati; Unik Hanifah Salsabila; Indah Purwanda; Nasirudin Ahmad; Caya Tri Jaka (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
Islamic education technology has an important role in Islamic education. Islamic education technology offers various facilities for the world of education. Pesantren should participate in following the progress of the times. Islamic boarding schools can take advantage of educational technology and the advancement of the times to further expand and develop educational and Islamic knowledge and can broadcast Islamic education more. In pesantren education, the role of educational technology is still not implemented. Islamic boarding schools tend to maintain their culture which some people consider ancient because they do not keep up with the times. This study used qualitative research methods. Materials are obtained from relevant sources in the form of books, scientific articles, and journals. In the study, it was found that Islamic boarding schools trying to keep up with the current changing times. Islamic boarding schools try to adopt the various advances of the times while still prioritizing the religious teachings that apply in the pesantren. With this, pesantren need not be afraid to progress and develop.